Uji Usability Dengan Metode Cognitive Walkthrough Pada Situs Web Perpustakaan Universitas Mercu Buana Jakarta - Priyo Raharjo; Wisnu Ananta Kusuma; Heru Sukoco (Jurnal Pustakawan Indonesia, 2016)
Creating a university library’s website needs to pay attention to usability aspect as a key of success and also as a user requirement for a website existence. The purpose of this research is to identify and analyze what problem would user facing and also giving a recommendation for maintenance in website’s interface to become more user-friendly. In this research, we did usability test to Universitas Mercu Buana library’s website using cognitive walkthrough method. A Cognitive walkthrough is a method to test usability where tester does series of task scenario to reach its goal. Usability test component covers effectiveness and efficiency. The result of this testing shows that the rate of finished task scenario from respondent are 90%. The Margin of error in this task scenario are from downloading from ProQuest database article. The average time for respondent completes all the task scenario is 680 seconds. The problem that users facing when using the website are finding book title, downloading thesis, finding journal title, finding article title, and downloading article from ProQuest database. the improvement this website need are adding the new search filter for ProQuest database article, the search box should be on every web pages, collection availability status should be showing in the search result without clicking title or call number, and term naming should be relevant to the content.Keywords: Cognitive Walkthrough, Library Website, Usability, Usability Testing, Website